PENGEMBANGAN ENSIKLOPEDIA BERMUATAN QUIZ GAME PADA MATERI KERAGAMAN DI INDONESIA KELAS IV SDIT DARUSSALAM - Rahmadhania, Raihannisa Asri; Sapti, Mujiyem; Pangestika, Rintis Rizkia (Dharmas Education Journal (DE_Journal), 2024)
This research aims to (1) Describe the steps in developing an encyclopedia. (2) Feasibility of an Encyclopedia Containing a Quiz Game on Diversity in Indonesia for Class IV SDIT Darussalam. The ADDIE research method has 5 stages, namely analysis, design, development, implementation, and evaluation. This research instrument uses teaching modules. The result of the research show that: (a) Validity is seen from the material expert’s response which received a percentage of 93,3% and the media expert’s response which received a percentage 0f 93,3% so that a very valid category was obtained. (b) Feasibility is seen from the educators’ responses which received a percentage of 95,8% in the very feasible category. (c) Practicality is obtained from student responses with the results of limited trials getting a percentage of 92,2%, extensive trials getting a percentage of 91,7% and learning implementation tests getting a percentage of 97% (observer 1) and 96,25% (observer 2) so it gets a very practical category. (d) Effectiviness is obtained from the test result of students who got a percentage of 89,2% so they got the very effective category.